The Mediating Role of Problematic Use of Loot Boxes Between Internet Gaming Disorder and Online Gambling Disorder: Cross-Sectional Analytical Study - Joaquín González-Cabrera; Vanessa Caba-Machado; Adoración Díaz-López; Susana Jiménez-Murcia; Gemma Mestre-Bach; Juan M Machimbarrena (JMIR Publications, 2024)
Abstract BackgroundThe video game industry has introduced a new form of monetization through microtransactions. A controversial example has been the so-called "loot boxes" (LBs) as virtual objects, which are randomized and bought with legal money. In recent years, LBs have come to connect 2 distinct problem behaviors, namely internet gaming disorder (IGD) and online gambling disorder (OGD). Many association studies have been conducted on the 3 constructs, but few have delved into the relationship of problematic use of LBs (PU-LB) with IGD and OGD. ObjectiveThis study aims to explore the mediating role of the PU-LB between IGD and OGD. MethodsThis cross-sectional and analytical study used incidental sampling in 24 Spanish schools. The final sample consisted of 542 participants (male: n=523, 96.5%; age: range 11‐30 y) who played video games, bought LBs, and had gambled online in the last 12 months. Participants then completed the Spanish versions of the Internet Gaming Disorder Scale-Short Form, Online Gambling Disorder Questionnaire, and PU-LB scale. ResultsIGD scores were found to be significantly associated with both PU-LB (rPrPrPPP ConclusionsIt is suggested that there is a mediation effect of problematic LB use between internet gambling and online gambling problems in both minors and young adults. This has potential practical implications by providing more evidence on how LBs have become a hinge feature between 2 clinically relevant and independent issues. In this regard, adequate industry self-regulation is needed, and effective legislation for the protection of minors is necessary.